2023
DOI: 10.3390/jfb14020074
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Based on Nanoclay and Gelatin Methacrylate Polymeric Matrix as a Potential Osteogenic Application

Abstract: A nanocomposite hydrogel has potentially applicability in the induction of osteogenesis. The hydrogel was synthesized using 1% gelatin methacrylate (GelMA), a biodegradable and bioactive polymer containing the structure of gelatin, denatured collagen derived from the extracellular bone matrix, and 6% laponite (Lap), a synthetic phyllosilicate of nanosized particles. Initially, 0.6 g of Lap was added to deionized water, and then a solution of GelMA/Igarcure was added under stirring and UV light for crosslinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Itaconate-encapsulated ZIF-8 NPs immobilized in GelMA [159], Curcumin-incorporated GelMA [160], Methacrylated chondroitin sulfate/ methacrylated HA/GelMA [161]. Adipose-derived stromal/stem cells-incorporated GelMA/MAAmodified poly(amidoamine) [162], GelMA/ engineered cartilage gel [163], Diclofenac sodium-incorporated GelMA/acrylamide/2methacryloyloxyethyl phosphorylcholine [97], bMSCs affinity peptide sequence PFSSTKT-modified chondrocyte ECM particles/GelMA [164], Nanoclay/alginate/GelMA [165], Denatured collagen/Gel-MA/Laponite [166], Iron oxide NPs/GelMA [167], Alanyl-Glutamine-modified GelMA [168] are some of the recent studies that demonstrated favorable results in cartilage tissue repair.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Itaconate-encapsulated ZIF-8 NPs immobilized in GelMA [159], Curcumin-incorporated GelMA [160], Methacrylated chondroitin sulfate/ methacrylated HA/GelMA [161]. Adipose-derived stromal/stem cells-incorporated GelMA/MAAmodified poly(amidoamine) [162], GelMA/ engineered cartilage gel [163], Diclofenac sodium-incorporated GelMA/acrylamide/2methacryloyloxyethyl phosphorylcholine [97], bMSCs affinity peptide sequence PFSSTKT-modified chondrocyte ECM particles/GelMA [164], Nanoclay/alginate/GelMA [165], Denatured collagen/Gel-MA/Laponite [166], Iron oxide NPs/GelMA [167], Alanyl-Glutamine-modified GelMA [168] are some of the recent studies that demonstrated favorable results in cartilage tissue repair.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…16,17 However, inferior weight-bearing properties of GelMA limit their use and need to be reinforced with certain components, including carbon nanotubes, nano-cellulose, and nano clay to enhance the mechanical properties. [18][19][20] To take advantage of GelMA cell adhesion properties, there are few current reports that utilized GelMA coating on 3D printed polymeric scaffolds that improve the cell behavior. 21,22 The 3D bioprinting of fiber-reinforced GelMA hydrogel offers advantages including patient specificity or cell patterning, which are still missing.…”
Section: Introductionmentioning
confidence: 99%